Poor Parental Supervision Associated With Traumatic Brain Injury and Reactive Aggression in Young Offenders. Issue 2 (22nd March 2022) - Kent, Hope; Williams, W. Huw; Hinder, Darren; Meadham, Hannah; Hodges, Emma; Agarwalla, Vedika; Hogarth, Lee; Mewse, Avril J.
Abstract : Objective: To establish whether poor parental supervision is associated with head injury and self-reported reactive aggression (ie, aggression in response to perceived provocation or threat) in adolescents in a Young Offender's Institute, by examining correlations between these variables. Understanding this population is important, as they are at a key pivotal age for intervention to prevent lifelong reoffending. Methods: Ninety-six male participants aged 16 to 18 years were recruited from a UK Young Offender's Institute. Self-report measures of remembered parenting, reactive aggression, and head injury history were administered during individual interviews. Results: Seventy-four percent of participants reported having experienced a lifetime traumatic brain injury (TBI), and 46% of participants reported experiencing at least 1 TBI leading to a loss of consciousness (LOC). We found that poor parental supervision, length of LOC following TBI, and self-reported reactive aggression were all positively correlated. Conclusions: Findings show that there are correlational relationships between poor parental supervision, length of LOC following lifetime TBI, and higher levels of self-reported reactive aggression. This suggests there may be pathways resulting from poor parental supervision leading to both TBI with LOC, and reactive aggression. We advocate for future research with longitudinal designs and larger samples to examine the nature of these interactions, and to establish whether poor parental supervision is a prospective risk factor for more TBIs leading to LOC, and reactive aggression. This is key to understanding whether parenting interventions could help to reduce the disabling effects of TBI in adolescents, and help to prevent contact with the law.